PENGARUH KEJELASAN SASARAN ANGGARAN, ETIKA, DAN KEPERCAYAAN DIRI PADA SENJANGAN ANGGARAN - Biantara, Anak Agung Adi; Dwija Putri, IG.A.M Asri (E-Jurnal Akuntansi, 2014)
Budget on the public sector with regard to the determination of the amount of funds allocated to each program and structured activities which use the funds belonging to the community. Good budgeting requires the participation of members of the organization. This study outlines the influence of Clarity Target Budget, Ethics, and Self Esteem In Budgetary Slack In Badung Regency Government. The population in this study was 684 competent authorities in the preparation of the budget in Badung Regency Government. The data was collected using a questionnaire with a random sampling method. Based on the analysis it was found that the variable budget goal clarity has a positive effect on the budgetary slack, variable ethics, and self esteem negative effect on the budgetary slack.
Keywords: budget: ethics: and self esteem